Risk of developing juvenile idiopathic arthritis after quadrivalent HPV vaccination: a retrospective cohort study using the TriNetX U.S. Network - Wu, Wen-Yu; Chen, Hsin-Hua; Tsai, Ming-Chin; Huang, Yung-Chieh; Chen, Jun-Peng; Fu, Lin-Shien (Frontiers in Immunology, 2025)
IntroductionHuman papillomavirus (HPV) infection has been implicated in autoimmune processes, yet concerns remain about the potential autoimmune risks of HPV vaccination. Juvenile idiopathic arthritis (JIA) is a chronic autoimmune condition that typically manifests in childhood. The relationship between HPV vaccination and the development of JIA remains uncertain.MethodsWe conducted a retrospective cohort study using data from the TriNetX U.S. Collaborative Network. Females aged 9–13 years were included. Three analyses were performed: (1) comparing HPV4-vaccinated vs. unvaccinated matched cohorts; (2) a stricter comparison excluding subjects with positive ANA; (3) comparing single vs. multiple HPV4 doses. Propensity score matching and Cox proportional hazards models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs).ResultsIn Analysis 1 (n=55,257 pairs) and Analysis 2 (n=53,827 pairs), the HPV4-vaccinated groups showed significantly reduced rates of JIA from 12 to 36 months post-vaccination (HR range: 0.33–0.52). No difference in JIA risk was observed between single and multiple doses in Analysis 3 (n=20,822 pairs). Early-onset JIA (<6 months after HPV4 vaccine) showed inconsistent trends, with only limited protective signals.ConclusionsOur findings suggest that HPV4 vaccination is not associated with an increased risk of JIA. On the contrary, vaccination may confer a long-term protective effect against new-onset JIA, observable from 6–12 months and lasting for at least 3 years. These findings support the safety and possible immunoregulatory benefit of HPV4 in adolescents.